WAYS OF DEVELOPMENT OF PERFORMING ART IN THE MASTER-APPRENTICE TRADITION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This scientific article describes the achievements in performing arts in detail and the continuation of the mastership path. Today, there has been an attempt to showcase the secrets of masterful music in the performing arts, with the ability to listen to masterful musical instruments and to perform them in a professional way. In this article we are going to deal with performance issues.